Acute phase proteins in diagnostics: more than expected - CERON, J. J.; MARTINEZ-SUBIELA, S.; TECLES, F.; CALDIN, M. (Journal of the Hellenic Veterinary Medical Society, 2017)
The objective of this review is to provide updated information about how acute phase proteins (APPs) can be used in the process of diagnosis in veterinary medicine. For this purpose, recommendations about assay methodologies and basic principles regarding clinical application of APPs will be provided. In addition, the use of APPs for (1) the detection and quantification of inflammatory response, (2) the diagnosis of the underlying etiology and (3) the detection of selected non-inflammatory processes will be reviewed with practical examples.